Virus inactivation structure
By using polyamide branch structures with ionic groups, nonionic water affinity groups and electron donor groups, the problem of difficult to provide long-term effective high virus neutralization functions in the prior art is solved, and efficient neutralization of a variety of viruses, especially enveloped viruses, is achieved.
Patent Information
- Application Number
- JP2021061601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-03-31
AI Technical Summary
The prior art is difficult to provide a viral neutralization structure with high viral neutralization function and long-term effective.
A virus neutralization structure is adopted which consists of a polyamide branch structure consisting of an ionic group, a nonionic water shady affinity group and an electron donation, where the polyamide branch is composed of multiple polymer chains, which have a specific functional group and are connected to the matrix to form a branch structure.
An efficient virus neutralization function is achieved, and this function can be maintained for a long time and effectively fights against a variety of viruses, especially enveloped viruses.
Smart Images

Figure 0007664607000004 
Figure 0007664607000005 
Figure 0007664607000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a virus inactivating structure that has a high virus inactivating function and can sustain this high virus inactivating function over a long period of time. [Background technology]
[0002] Many viral diseases such as influenza, measles, and chickenpox are easily transmitted by viruses attached to familiar objects, droplet infection, droplet nucleus infection, etc. Therefore, measures against viral infection are a major issue in modern society. As an attempt to counter viral infection, for example, Patent Document 1 proposes a compound having a virus inactivating effect.
[0003] On the other hand, the global spread of the novel coronavirus (COVID-19) has become a major issue that demands changes to social life, and from the perspective of quickly and stably calming the global spread of viral infections such as the novel coronavirus (COVID-19), there is a strong demand for materials that have high virus inactivation properties and can maintain this high virus inactivation property over the long term. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-128342 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a virus inactivating structure that has a high virus inactivating function and can sustain this high virus inactivating function for a long period of time. [Means for solving the problem]
[0006] As a result of intensive research to achieve the above-mentioned object, the inventors have discovered that a polymer brush structure containing a plurality of polymer chains having functional groups selected from ionic groups, nonionic hydrophilic groups, and electron-donating groups has a high virus inactivation function and furthermore can maintain this high virus inactivation function for a long period of time, thereby completing the present invention.
[0007] That is, the present invention relates to the following: [1] A virus inactivation structure having a virus inactivation function, which has a polymer brush structure including a plurality of polymer chains having functional groups selected from ionic groups, nonionic hydrophilic groups, and electron-donating groups. [2] The virus inactivating structure according to [1], wherein the plurality of polymer chains are water-soluble. [3] The virus inactivating structure according to [1] or [2], wherein a plurality of the polymer chains are covalently fixed onto a substrate to form a polymer brush structure. [4] The average molecular chain length L of the polymer chains constituting the polymer brush structure p , the thickness T of the polymer brush structure b Ratio of (T b / L p ) is 0.001 to 0.6. [5] The virus inactivation structure according to [3] or [4], wherein the substrate is a fiber, a monofilament, a twisted yarn, a woven fabric, a nonwoven fabric, a cut fiber, a hollow fiber, glass, a metal, or a processed product thereof. [6] The virus inactivation structure according to [1] or [2], wherein at least one end of each of the polymer chains is present in the base polymer and at least a portion of the polymer chains is exposed from the base polymer, thereby forming a polymer brush structure. [7] The virus inactivating structure according to [1] or [2], wherein the multiple polymer chains are polymer graft chains branched from a main polymer chain, thereby forming a bottle-brush-shaped polymer brush structure. [8] The ionic conductivity of the polymer brush structure is 5.0 × 10 -1The virus inactivating structure according to any one of [1] to [7], wherein the viscosity is S / m or less. [9] The virus inactivating structure according to any one of [1] to [8], wherein a plurality of the polymer chains have ammonium groups. Effect of the Invention
[0008] According to the present invention, it is possible to provide a virus inactivating structure that has a high virus inactivating function and can sustain that high virus inactivating function for a long period of time. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a virus inactivating structure according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing a virus inactivating structure according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a diagram showing a virus inactivating structure according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The virus inactivating structure of the present invention has a polymer brush structure containing a plurality of polymer chains having specific functional groups selected from ionic groups, nonionic hydrophilic groups, and electron-donating groups, and has a virus inactivating function. The present inventors conducted extensive research and found that a polymer brush structure containing multiple polymer chains having specific functional groups selected from ionic groups, nonionic hydrophilic groups, and electron-donating groups has high virus inactivation properties and furthermore maintains this virus inactivation function for a long period of time, which led to the completion of the present invention. In particular, the present inventors were the first to discover that such an effect is unique to the polymer brush structure. Here, the polymer brush structure may be any structure that includes multiple polymer chains that are physically or chemically fixed to a substrate, and as long as it is such a structure, its shape, etc. are not particularly limited.
[0011] First Embodiment First, a first embodiment of the present invention will be described. Fig. 1 is a diagram showing a virus inactivation structure according to a first embodiment of the present invention. As shown in Fig. 1, the virus inactivation structure according to the first embodiment is composed of a substrate 10 and a polymer brush layer 20 formed on the substrate 10.
[0012] The substrate 10 is not particularly limited, and may be a wide variety of materials such as fibers, monofilaments, twisted yarns, woven fabrics, nonwoven fabrics, cut fibers, hollow fibers, glass, metals, or processed products thereof. It may also be particles such as silica or carbon black. In particular, according to the present invention, by using a substrate 10 of any material and having any shape and forming a polymer brush layer 20 on its surface, it is possible to impart the virus inactivation effect of the polymer brush layer 20 to any material of any shape.
[0013] The polymer brush layer 20 is a layer containing a plurality of polymer chains covalently fixed onto the base material 10 as a substrate, and in the present invention, the polymer brush layer 20 is formed from polymer chains having a specific functional group (hereinafter referred to as the “specific functional group” as appropriate) selected from an ionic group, a nonionic hydrophilic group, and an electron-donating group.
[0014] In the present invention, the reason why polymer brush layer 20 exhibits an inactivating effect on viruses is not necessarily clear, but the following reason is thought to be the case. That is, when a virus adheres to the surface of polymer brush layer 20, a thermodynamic micelle fusion phenomenon causes multiple polymer chains having specific functional groups that make up polymer brush layer 20 to fuse with the envelope that makes up the virus (pseudo-infection), causing the envelope to cleave. It is thought that the RNA inside the virus is then expelled to the outside by the high osmotic pressure of the polymer chains having specific functional groups, thereby inactivating the virus.
[0015] In the present invention, the polymer brush layer 20 is composed of a plurality of polymer chains having specific functional groups, and the presence of such specific functional groups makes it easy to fuse with the envelope that constitutes the virus, and furthermore, being composed of a plurality of polymer chains, it exhibits high osmotic pressure, which can be said to provide a high level of virus inactivation function. Furthermore, since the polymer brush layer 20 has a structure composed of a plurality of polymer chains, it can stably provide such a high level of virus inactivation function without accompanying structural changes, and therefore it can be said that the high level of virus inactivation function can be sustained for a long period of time.
[0016] Therefore, according to the present invention, a high inactivation effect is achieved against various viruses, particularly against enveloped viruses. As described above, in the present invention, it is considered that a plurality of polymer chains having specific functional groups constituting the polymer brush layer 20 fuse with the envelope constituting the virus (pseudo-infection) and cleave the envelope, and the envelope constituting the virus is generally composed of a phospholipid bilayer membrane. In contrast, fungi such as bacteria have a cell membrane composed of polysaccharides, etc., and in this respect, viruses and fungi such as bacteria are completely different, and furthermore, their size and characteristics are completely different from those of viruses. In particular, while those that exhibit bactericidal or antibacterial effects generally destroy cell membranes composed of polysaccharides, etc. (i.e., act on polysaccharides), in the present invention, it is considered that the effect is to fuse with and cleave an envelope composed of a phospholipid bilayer membrane (i.e., act on a phospholipid bilayer membrane), and therefore, the mechanism of action and required characteristics are considered to be different from those that exhibit bactericidal or antibacterial effects.
[0017] The multiple polymer chains constituting the polymer brush layer 20 have, as the specific functional group, a functional group selected from an ionic group, a nonionic hydrophilic group, and an electron-donating group.
[0018] The ionic group is not particularly limited and may be either a cationic functional group or an anionic functional group, and examples thereof include an ammonium group, a sulfonic acid group, a sulfonimide group, a sulfate group, a phosphonic acid group, a phosphoric acid group, a carboxylic acid group, an acrylic acid group, a methacrylic acid group, or salts thereof, and salts of a hydroxyl group, a thiol group, etc.
[0019] In addition, when the ionic group is a cationic functional group, it usually forms a salt structure together with a counter anion, and when the ionic group is an anionic functional group, it usually forms a salt structure together with a counter cation. The counter anion is not particularly limited, but may be BF4 - , PF6 - , AsF6 - , SbF6 - , AlCl4 - , NbF6 - , HSO4 - , ClO4 - , CH3SO3 - , CF3SO3 - , CF3CO2 - , (CF3SO2)2N - , Cl - , Br - , I - The counter cation is not particularly limited, but may be Na + , K + , Li + Alkali metal ions such as Ca 2+ , Mg 2+ and the like; organic cations such as ammonium ion and alkylammonium ion; and the like.
[0020] The nonionic hydrophilic group is not particularly limited, but examples thereof include a hydroxyl group, an amide group, an amino group, an ether bond, and a thiol group.
[0021] The electron-donating group may be any group that exhibits electron-donating properties and does not fall under the category of the above-mentioned ionic groups and nonionic hydrophilic groups, and examples thereof include groups containing a nitrogen atom, an oxygen atom, a sulfur atom, a silicon atom, a phosphorus atom, etc., and specific examples thereof include a hydroxy group, an amino group, a methoxy group, and a sulfide group.
[0022] Among the specific functional groups described above, from the viewpoint of having a higher affinity for the virus envelope and therefore exhibiting a higher virus inactivation function, ionic groups and nonionic hydrophilic groups are preferred, ionic groups are more preferred, cationic functional groups are even more preferred, and ammonium groups are more preferred. Note that the multiple polymer chains constituting the polymer brush layer 20 may contain only one type of specific functional group or two or more types.
[0023] Furthermore, the multiple polymer chains constituting the polymer brush layer 20 are preferably composed of polymers that exhibit water-solubility. In particular, when the polymer brush layer 20 contains a trace amount of moisture or is wet with water (a state in which the polymer brush layer 20 is a layer that retains water), from the viewpoint of high virus adhesion and therefore of being able to inactivate viruses with high efficiency, the multiple polymer chains constituting the polymer brush layer 20 are preferably composed of polymers that exhibit water-solubility. In the present invention, a polymer may be determined to be water-soluble if it exhibits water-solubility anywhere in the pH range of 1 to 12 (for example, if the absorbance is 0.3 or less when 1 wt % of the polymer is dispersed in water).
[0024] The polymer brush layer 20 can be formed, for example, by fixing a plurality of polymer chains onto the substrate 10 by covalent bonds, and more specifically, by introducing polymer chains onto the surface of the substrate 10 by a surface-initiated living radical polymerization method.
[0025] The surface-initiated living radical polymerization method is a technique for forming a polymer chain (polymer graft chain) by introducing a polymerization initiating group into the surface of the substrate 10, which is the starting point of the polymer chain, and performing living radical polymerization using the polymerization initiating group as the starting point. For example, the methods described in JP-A-2009-59659 and JP-A-2010-218984 can be applied.
[0026] The monomer for forming the polymer chain is not particularly limited, and at least one of the monomers having the specific functional group described above may be used. However, a monomer having an ammonium group as the specific functional group is preferable, and a monomer capable of introducing an ammonium group into the side chain of the polymer chain is more preferable (i.e., it is more preferable that the multiple polymer chains constituting the polymer brush layer 20 have an ammonium group in the side chain). For example, a compound represented by the following general formula (1) is an example of a monomer having an ammonium group as the specific functional group. The monomer having the specific functional group may be used alone or in combination of two or more kinds. Furthermore, a monomer copolymerizable with the monomer having the specific functional group (monomer not having the specific functional group) may be used as the monomer for forming the polymer chain. [ka] In the above general formula (1), m represents an integer of 1 or more and 10 or less, and n represents an integer of 1 or more and 5 or less. 1 R represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 2 , R 3 , R 4 R represents an alkyl group having 1 to 5 carbon atoms. 2 , R 3 , R 4 may contain one or more heteroatoms selected from an oxygen atom, a sulfur atom, and a fluorine atom; R 2 , R 3 , R 4 may be linked to form a ring structure. - represents a monovalent anion.
[0027] The monovalent anion Z in the above general formula (1) - The above is not particularly limited, and examples thereof include BF4 - , PF6 - , AsF6 - , SbF6 - , AlCl4 - , NbF6 - , HSO4 - , ClO4 - , CH3SO3 - , CF3SO3 - , CF3CO2 - , (CF3SO2)2N - , Cl - , Br - , I - Anions such as BF4 can be used. - , PF6 - , (CF3SO2)2N - , CF3SO3 - , or CF3CO2 - It is preferable that:
[0028] Among the compounds represented by the above general formula (1), the compounds represented by the following general formulas (2) to (9) are particularly suitable for use from the viewpoint of their high virus inactivation effect. These compounds may be used alone or in combination of two or more. [ka] [In the above general formulas (2) to (9), n, m, R 1 , R 2 , Z - is the same as in the above general formula (1).
[0029] As the monomer used to form the polymer chain, instead of the compound represented by the above general formula (1) or together with the compound represented by the above general formula (1), for example, a (meth)acrylic acid-based monomer, a styrene-based monomer, a monofunctional monomer having one addition-polymerizable double bond, a hydrophobic monomer, a hydrophilic monomer, a monomer having a carboxyl group or a group that can be easily converted to a carboxyl group in the side chain, and the like can be used.
[0030] Specific examples of (meth)acrylic acid monomers include: (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate; heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, benzyl (meth)acrylate; 2-Methoxyethyl (meth)acrylate, 3-Methoxypropyl (meth)acrylate, 3-Methoxybutyl (meth)acrylate, 2-Hydroxyethyl (meth)acrylate, 2-Hydroxypropyl (meth)acrylate, Stearyl (meth)acrylate, Glycidyl (meth)acrylate, 3-Ethyl-3-(meth)acryloyloxymethyloxetane; 2-(meth)acryloyloxyethyl isocyanate, (meth)acrylate-2-aminoethyl, 2-(2-bromopropionyloxy)ethyl (meth)acrylate, 2-(2-bromoisobutyryloxy)ethyl (meth)acrylate; 1-(meth)acryloxy-2-phenyl-2-(2,2,6,6-tetramethyl-1-piperidinyloxy)ethane, 1-(4-((4-(meth)acryloxy)ethoxyethyl)phenylethoxy)piperidine, γ-(methacryloyloxypropyl)trimethoxysilane; 3-(3,5,7,9,11,13,15-heptaethylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)propyl (meth)acrylate, 3-(3,5,7,9,11,13,15-heptaisobutyl-pentacyclo[9.5.1.13,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)propyl (meth)acrylate, 3-(3,5,7,9,11,13,15-heptaisooctylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxane-1-yl)propyl (meth)acrylate; 3-(3,5,7,9,11,13,15-heptacyclopentylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)propyl (meth)acrylate, 3-(3,5,7,9,11,13,15-heptaphenylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)propyl (meth)acrylate, 3-[(3,5,7,9,11,13,15-heptaethylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl]propyl(meth)acrylate; 3-[(3,5,7,9,11,13,15-heptaisobutylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yloxy)dimethylsilyl]propyl (meth)acrylate, 3-[(3,5,7,9,11,13,15-heptaisooctylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl]propyl(meth)acrylate; 3-[(3,5,7,9,11,13,15-heptacyclopentylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13]octasiloxane-1-yloxy)dimethylsilyl]propyl (meth)acrylate, 3-[(3,5,7,9,11,13,15-heptaphenylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl]propyl(meth)acrylate; Ethylene oxide adduct of (meth)acrylic acid, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, trifluoromethyl (meth)acrylate, diperfluoromethylmethyl (meth)acrylate; 2-perfluoromethyl-2-perfluoroethylethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, 2-perfluorohexadecylethyl (meth)acrylate; and the like.
[0031] Specific examples of styrene monomers include: Styrene, vinyltoluene, α-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, m-chloromethylstyrene, o-aminostyrene, p-styrene chlorosulfonic acid, styrenesulfonic acid and its salts, vinylphenylmethyldithiocarbamate, 2-(2-bromopropionyloxy)styrene, 2-(2-bromoisobutyryloxy)styrene; 1-(2-((4-vinylphenyl)methoxy)-1-phenylethoxy)-2,2,6,6-tetramethylpiperidine, 1-(4-vinylphenyl)-3,5,7,9,11,13,15-heptaethylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasilosiloxane, 1-(4-vinylphenyl)-3,5,7,9,11,13,15-heptaisobutylpentacyclo[9.5.1.1 3,9 .15,15 .1 7,13 ]Octasiloxane; 1-(4-vinylphenyl)-3,5,7,9,11,13,15-heptaisooctylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane, 1-(4-vinylphenyl)-3,5,7,9,11,13,15-heptacyclopentyl pentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasilosiloxane, 1-(4-vinylphenyl)-3,5,7,9,11,13,15-heptaphenylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxane; 3-(3,5,7,9,11,13,15-heptaethylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)ethylstyrene, 3-(3,5,7,9,11,13,15-heptaisobutylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)ethylstyrene, 3-(3,5,7,9,11,13,15-heptaisooctylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxane-1-yl)ethylstyrene; 3-(3,5,7,9,11,13,15-heptacyclopentylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)ethylstyrene, 3-(3,5,7,9,11,13,15-heptaphenylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yl)ethylstyrene, 3-(3,5,7,9,11,13,15-heptaethylpentacyclo[9.5.1.1 3,9 .1 5,15.1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl)ethylstyrene; 3-(3,5,7,9,11,13,15-heptaisobutylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl)ethylstyrene, 3-(3,5,7,9,11,13,15-heptaisooctylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]Octasiloxan-1-yloxy)dimethylsilyl)ethylstyrene; 3-((3,5,7,9,11,13,15-Heptacyclopentylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yloxy)dimethylsilyl)ethylstyrene, 3-((3,5,7,9,11,13,15-heptaphenylpentacyclo[9.5.1.1 3,9 .1 5,15 .1 7,13 ]octasiloxane-1-yloxy)dimethylsilyl)ethylstyrene; and the like.
[0032] Specific examples of monofunctional monomers having one addition-polymerizable double bond include: Fluorine-containing vinyl monomers (perfluoroethylene, perfluoropropylene, vinylidene fluoride, etc.), silicon-containing vinyl monomers (vinyltrimethoxysilane, vinyltriethoxysilane, etc.), maleic anhydride, maleic acid, monoalkyl esters and dialkyl esters of maleic acid, fumaric acid, monoalkyl esters and dialkyl esters of fumaric acid; Maleimide monomers (maleimide, methylmaleimide, ethylmaleimide, propylmaleimide, butylmaleimide, hexylmaleimide, octylmaleimide, dodecylmaleimide, stearylmaleimide, phenylmaleimide, cyclohexylmaleimide, etc.); Nitrile group-containing monomers (acrylonitrile, methacrylonitrile, etc.), amide group-containing monomers (acrylamide, methacrylamide, etc.), vinyl ester monomers (vinyl acetate, vinyl propionate, vinyl pivalate, vinyl benzoate, vinyl cinnamate, etc.); Olefins (ethylene, propylene, etc.), conjugated diene monomers (butadiene, isoprene, etc.), vinyl halides (vinyl chloride, etc.), vinylidene halides (vinylidene chloride, etc.), allyl halides (allyl chloride, etc.); Allyl alcohol, vinylpyrrolidone, vinylpyridine, N-vinylcarbazole, methyl vinyl ketone, vinyl isocyanate, and the like. In addition, as the monofunctional monomer having one addition-polymerizable double bond, a macromonomer having one polymerizable double bond in one molecule and having a main chain derived from styrene, (meth)acrylic acid ester, siloxane, or the like can also be used.
[0033] Specific examples of hydrophobic monomers include: Acrylic acid esters (alkyl esters of acrylic acid such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, cyclohexyl acrylate, hexafluoroisopropyl acrylate, etc.; aryl acrylates such as phenyl acrylate; aryl alkyl acrylates such as benzyl acrylate; alkoxy alkyl acrylates such as methoxymethyl acrylate, etc.); Methacrylic acid esters (alkyl esters of methacrylic acid such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, hexafluoroisopropyl methacrylate, etc.; aryl methacrylates such as phenyl methacrylate; aryl alkyl methacrylates such as benzyl methacrylate; alkoxy alkyl methacrylates such as methoxy methyl methacrylate, etc.); Fumaric acid esters (e.g., alkyl esters of fumaric acid such as dimethyl fumarate, diethyl fumarate, diallyl fumarate, etc.), maleic acid esters (e.g., alkyl esters of maleic acid such as dimethyl maleate, diethyl maleate, diallyl maleate, etc.); Itaconic acid esters (such as alkyl esters of itaconic acid), crotonic acid esters (such as alkyl esters of crotonic acid), methyl vinyl ether, ethoxyethyl vinyl ether, vinyl acetate, vinyl propionate, vinyl benzoate, styrene; Examples thereof include alkyl styrene, vinyl chloride, vinyl methyl ketone, vinyl stearate, vinyl alkyl ether, and the like.
[0034] Specific examples of hydrophilic monomers include: Hydroxy-substituted alkyl acrylates (2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl acrylate, 2,3-dihydroxypropyl acrylate, polyethoxyethyl acrylate, polyethoxypropyl acrylate, etc.); Hydroxy-substituted alkyl methacrylates (2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxypropyl methacrylate, 2,3-dihydroxypropyl methacrylate, polyethoxyethyl methacrylate, polyethoxypropyl methacrylate, etc.); Acrylamide, N-alkylacrylamides (N-methylacrylamide, N,N-dimethylacrylamide, etc.), N-alkylmethacrylamides (N-methylmethacrylamide, etc.); Polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxypolyethylene glycol acrylate, alkoxypolyethylene glycol methacrylate, phenoxypolyethylene glycol acrylate, phenoxypolyethylene glycol methacrylate, 2-glucosyloxyethyl methacrylate; Examples of the monomer include acrylic acid, methacrylic acid, fumaric acid, maleic acid, itaconic acid, crotonic acid, methacrylamide, allyl alcohol, N-vinylpyrrolidone, and N,N-dimethylaminoethyl acrylate.
[0035] Specific examples of monomers having a carboxyl group or a group that can be easily converted to a carboxyl salt group on the side chain include: 1-Methoxyethyl acrylate, 1-ethoxyethyl acrylate, 1-propoxyethyl acrylate, 1-(1-methylethoxy)ethyl acrylate, 1-butoxyethyl acrylate, 1-(2-methylpropoxy)ethyl acrylate, 1-(2-ethylhexoxy)ethyl acrylate; Pyranyl acrylate, 1-methoxyethyl methcrete, 1-ethoxyethyl methcrete, 1-propoxyethyl methcrete, 1-(1-methylethoxy)ethyl methcrete, 1-butoxyethyl methcrete, 1-(2-methylpropoxy)ethyl methcrete, 1-(2-ethylhexoxy)ethyl methacrylate; Pyranyl methacrylate, di-1-methoxyethyl malate, di-1-ethoxyethyl malate, di-1-propoxyethyl malate, di-1-(1-methylethoxy)ethyl malate, di-1-butoxyethyl malate, di-1-(2-methylpropoxy)ethyl malate, dipyranyl malate, and the like.
[0036] In addition, when polymerization is performed by the surface-initiated living radical polymerization method, the polymerization initiation group to be introduced onto the surface of the substrate 10 is not particularly limited as long as it can initiate polymerization, but halogenated alkyl groups, halogenated sulfonyl groups, etc. are preferred.
[0037] From the viewpoint of controllability of the graft density and the primary structure of the grafted polymer chain (molecular weight, molecular weight distribution, monomer arrangement pattern), it is preferable that the polymerization initiation group is physically or chemically bonded to the surface of the substrate 10.
[0038] Methods for introducing (binding) the polymerization initiation group to the surface of the base material 10 include chemical adsorption and Langmuir-Blodgett (LB) methods.
[0039] For example, when a silicon wafer is used as the substrate 10, fixation of a chlorosulfonyl group (polymerization initiating group) onto the silicon wafer surface by chemical bonding can be carried out by reacting the oxidized layer on the silicon wafer surface with 2-(4-chlorosulfonylphenyl)ethyltrimethoxysilane, 2-(4-chlorosulfonylphenyl)ethyltrichlorosilane, or the like.
[0040] In addition, when introducing a polymerization initiating group for surface-initiated living radical polymerization onto the surface of the substrate 10, it is preferable to use a polymerization initiating group-containing surface treatment agent that includes a polymerization initiating group and a group that has a binding property to the substrate or a group that has an affinity to the substrate. Such a polymerization initiating group-containing surface treatment agent may be a low molecular weight compound or a high molecular weight compound.
[0041] The polymerization initiator group-containing surface treatment agent is not particularly limited, but a compound having a group capable of bonding to the substrate 10 and a radical generating group is preferred. For example, a polymerization initiator group-containing surface treatment agent disclosed in JP-A-2010-218984, i.e., a TEMPO-based, ATRP-based, RAFT-based, or RTCP-based polymerization initiator group-containing surface treatment agent can be used. Among these, a TEMPO-based, RAFT-based, or RTCP-based polymerization initiator group-containing surface treatment agent is more preferred. Furthermore, among the TEMPO-based polymerization initiator group-containing surface treatment agents, a DEPN-based polymerization initiator group-containing surface treatment agent is particularly preferred. Examples of the group capable of bonding to the substrate 10 include -SiCl3, -Si(CH3)Cl2, -Si(CH3)2Cl, and -Si(OR)3 (wherein R represents methyl, ethyl, propyl, or butyl). Alternatively, as the polymerization initiator group-containing surface treatment agent, (2-bromo-2-methyl)propionyloxyhexyltriethoxysilane (BHE), (2-bromo-2-methyl)propionyloxypropyltriethoxysilane (BPE), etc., described in WO 2006 / 087839 can also be used.
[0042] From the viewpoint of adjusting the graft density, a silane coupling agent not containing a polymerization initiating group (for example, a commonly used alkylsilane coupling agent) may be used in combination with the above-mentioned surface treatment agent containing a polymerization initiating group.
[0043] The graft density can be freely changed by adjusting the ratio of the surface treatment agent containing a polymerization initiator group to the silane coupling agent not containing a polymerization initiator group. In addition, the LB method or the gas phase adsorption method can be adopted for the introduction of the polymerization initiator group to the surface of the substrate 10 in terms of the uniformity of the polymerization initiator group introduced and the controllability of the graft density of the polymerization initiator group.
[0044] In the LB method, the film-forming material is first dissolved in a suitable solvent (e.g., chloroform, benzene, etc.) Then, a small amount of this solution is spread on a clean liquid surface, preferably on the surface of pure water, and the solvent is then evaporated or diffused into an adjacent aqueous phase to form a low-density film of film-forming molecules on the water surface.
[0045] Subsequently, the partition plate is typically mechanically swept across the water surface to compress the film and increase its density by reducing the surface area of the water surface on which the film-forming molecules are spread, resulting in a dense monolayer on the water surface.
[0046] Next, under appropriate conditions, while maintaining constant the surface density of the molecules constituting the monolayer on the water surface, the substrate on which the monolayer is to be deposited is immersed or withdrawn in a direction across the monolayer on the water surface, thereby transferring the monolayer on the water surface onto the substrate 10, and the monolayer is deposited on the substrate.
[0047] Details and specific examples of the LB method are described in "Kiyonari Fukuda et al., New Experimental Chemistry Lectures, Vol. 18 (Interfaces and Colloids), Chapter 6, (1977), Maruzen," "Kiyonari Fukuda, Michio Sugi and Hiroyuki Suzumebe (eds.), LB Films and Electronics, (1986), CMC," and "Yoshio Ishii, Practical Techniques for Making Good LB Films, (1989), Kyoritsu Shuppan," etc.
[0048] Then, a polymerization initiator group is introduced onto the surface of the substrate 10 using the above-mentioned polymerization initiator, and then the substrate 10 into which the polymerization initiator group has been introduced is immersed in a polymerization reaction solution containing the above-mentioned monomer and heated as necessary, thereby forming a polymer chain containing the above-mentioned monomer as a polymerization unit on the surface of the substrate 10. Note that the polymerization reaction solution can contain components necessary for the polymerization reaction, such as various radical initiators and solvents, in addition to the above-mentioned monomers.
[0049] In the present invention, the polymer chains formed on the surface of the substrate 10 are preferably formed with a graft density such that the occupied area ratio (occupancy rate per polymer cross-sectional area) to the surface area of the substrate 10 is 0.1 to 50%, more preferably 10 to 45%, and even more preferably 20 to 40%. The graft density can be calculated from the absolute value of the number average molecular weight (Mn) of the polymer chains, the amount of grafted polymer, and the surface area of the substrate 10. The occupied area ratio in the polymer brush layer 20 can be calculated by multiplying the cross-sectional area obtained from the repeating unit length in the stretched form of the polymer and the bulk density of the polymer by the graft density. The occupied area ratio means the ratio of the surface of the substrate 10 occupied by the graft point (the first monomer) (100% in close packing, no more than this can be grafted). By setting the occupied area ratio of the polymer chains to the surface area of the substrate 10 within the above range, the virus inactivation function can be more appropriately enhanced; if the occupied area ratio is too low or too high, the virus inactivation function will be reduced.
[0050] According to the findings of the present inventors, the state of the polymer chains in polymer brush layer 20 does not necessarily need to be uniform, and may be a mixture of parts where the polymer chains are sparse and parts where the polymer chains are dense when viewed microscopically, and even in such an embodiment, the virus inactivation function can be sufficiently exhibited. Therefore, when measuring the above-mentioned exclusive area ratio, it is preferable that a relatively wide area range (specifically, an area range of 5 cm × 5 cm) on the surface of substrate 10 is measured, and when the measurement is performed, the exclusive area ratio is within the above-mentioned range.
[0051] The graft density of the polymer chains per unit area is preferably 0.0005 to 0.4 chains / nm 2 , more preferably 0.05 to 0.4 chains / nm 2 , and more preferably 0.1 to 0.4 chains / nm 2 、 Particularly preferably, the range is 0.12 to 0.25 chains / nm. 2 It is.
[0052] The graft density of the polymer chains can be measured according to the methods described in, for example, Macromolecules, 31, 5934-5936 (1998), Macromolecules, 33, 5608-5612 (2000), Macromolecules, 38, 2137-2142 (2005), etc. Specifically, the graft density (chains / nm 2 ) can be calculated by measuring the graft amount (W) and the number average molecular weight (Mn) of the graft chains and according to the following formula: Graft density (chains / nm 2 )=W(g / nm 2 ) / M n × (Avogadro's number) (In the formula, W represents the graft amount, and Mn represents the number average molecular weight.)
[0053] When the substrate 10 is a flat substrate, the graft amount (W) can be determined by measuring the dry film thickness, i.e., the thickness of the grafted polymer chain layer in a dry state, by ellipsometry, and calculating the graft amount per unit area using the density of the bulk film. Alternatively, when the substrate 10 is fibrous or the like, the graft amount (W) can be measured by infrared absorption spectroscopy (IR), thermogravimetric analysis (TG), elemental analysis, or the like.
[0054] The number average molecular weight (Mn) of the polymer chains constituting the polymer brush layer 20 is preferably 500 to 10,000,000, and more preferably 100,000 to 10,000,000. From the viewpoint of further enhancing the virus inactivation function, the molecular weight distribution (Mw / Mn) of the polymer chains constituting the polymer brush layer 20 is preferably close to 1, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.25 or less, even more preferably 1.2 or less, and particularly preferably 1.15 or less. The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer chains can be measured, for example, by cutting out the polymer chains from the substrate 10 by treatment with hydrofluoric acid, and measuring the cut out polymer chains by gel permeation chromatography in terms of polyethylene oxide. Alternatively, a method may be adopted in which, assuming that the free polymer produced during polymerization has a molecular weight equal to that of the polymer chain introduced into the substrate 10, the number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the free polymer are measured in terms of polyethylene oxide by gel permeation chromatography, and the results are used as is.
[0055] In addition, the average molecular chain length L of the polymer chains constituting the polymer brush layer 20 p (i.e., the polymer brush length) is preferably 10 nm or more, and from a practical point of view, it is more preferably in the range of 10 to 1000 nm. p If the average molecular chain length L of the polymer chain is too short, the virus inactivation function may be insufficient. p can be adjusted, for example, by the type of monomer constituting the polymer chain, polymerization conditions, etc.
[0056] The average molecular chain length L pcan be obtained, for example, by measuring the number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer chain and measuring the results. The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer chain can be measured, for example, by cutting out the polymer chain from the substrate 10 by hydrofluoric acid treatment and measuring the number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer chain by gel permeation chromatography using the cut polymer chain. Alternatively, a method may be adopted in which the free polymer generated during polymerization is assumed to have the same molecular weight as the polymer chain introduced into the substrate 10, the number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the free polymer are measured by gel permeation chromatography and used as is. The molecular weight distribution (Mw / Mn) of the polymer brush forming the first sliding surface is preferably close to 1, and is preferably 1.3 or less, more preferably 1.25 or less, even more preferably 1.2 or less, and particularly preferably 1.15 or less.
[0057] In addition, the average molecular chain length L p The thickness T of the polymer brush layer 20 b Ratio of (T b / L p ) is preferably 0.001 to 0.6, more preferably 0.1 to 0.6, further preferably 0.2 to 0.6, and particularly preferably 0.3 to 0.5. p The thickness T of the polymer brush layer 20 b Ratio of (T b / L p ) in the above range can further enhance the virus inactivation function.
[0058] The thickness T of the polymer brush layer 20 b The average molecular chain length L can be measured by spectroscopic ellipsometry after the polymer brush layer 20 is vacuum-dried at 25° C. for 1 hour to remove volatile matters, mainly including water. p The thickness T of the polymer brush layer 20 b Ratio of (T b / L p) is a value in a state where volatile components have been removed. Therefore, when polymer brush layer 20 contains volatile components such as moisture during use, the polymer chains constituting polymer brush layer 20 approach a fully extended state due to the inclusion of moisture, and the ratio (T b / L p ) may exceed the above range, but even in such a case, the ratio (T b / L p ) is preferably in the above range. For example, a polymer brush layer swollen with a non-volatile liquid such as a lubricating oil or an ionic liquid maintains the state of being swollen with the non-volatile liquid such as a lubricating oil or an ionic liquid even after the volatile components are removed. Therefore, even after the volatile components are removed, the ratio (T b / L p ) typically shows a large value of over 0.6.
[0059] The polymer brush layer 20 preferably has an ionic conductivity of 5.0×10 -1 S / m or less, and more preferably 1.0×10 -1 S / m or less, more preferably 5.0×10 -2 S / m or less, and although there is no particular lower limit, it is preferably 1.0×10 -4 S / m or more. That is, the polymer brush layer 20 does not substantially contain a liquid with a relatively high ionic conductivity (e.g., an ionic liquid, etc.), and therefore the ionic conductivity is low as in the above range. As a result, it is preferable that the polymer brush layer 20 is in a state in which it can contain moisture or in which it contains moisture, from the viewpoint of high virus adhesion and therefore high efficiency inactivation of viruses. Note that it is preferable that the ionic conductivity of the polymer brush layer 20 is in the above range either in a state in which it contains a volatile component such as moisture, or in a state in which it does not contain a volatile component such as moisture. The method for measuring the ionic conductivity of the polymer brush layer 20 is not particularly limited, but examples include a method of measuring conductivity by a four-terminal method (for example, measurement using a resistivity meter (Loresta, manufactured by Nitto Seiko Analytech Co., Ltd.)).
[0060] <Second embodiment> Next, a second embodiment of the present invention will be described. FIG. 2(A) is a diagram showing a virus inactivating structure according to a second embodiment of the present invention, FIG. 2(B) is a diagram showing the detailed structure of part IIb in FIG. 2(A), and FIG. 2(C) is a diagram showing the detailed structure of part IIc in FIG. 2(A).
[0061] 2(B), the virus inactivating structure according to the second embodiment of the present invention is formed by dispersing a plurality of block copolymer chains 40 in a base polymer 30. The plurality of block copolymer chains 40 each include a polymer block (A) and a polymer block (B) having a lower affinity for the base polymer 30 than the polymer block (A), and the block copolymer chain has the polymer block (A) in at least two locations.
[0062] In FIG. 2B, the polymer block (A) constituting the block copolymer chain 40 is indicated by a dashed line, and the polymer block (B) is indicated by a solid line. In FIG. 2B, an ABA type block copolymer chain consisting of polymer block (A) / polymer block (B) / polymer block (A) is illustrated as the block copolymer chain 40, but the structure is not limited to this structure as long as the structure has polymer block (A) at at least two positions. For example, the block copolymer chain may be an ABAB type block copolymer chain consisting of polymer block (A) / polymer block (B) / polymer block (A) / polymer block (B), or may be an ABABA type block copolymer chain consisting of polymer block (A) / polymer block (B) / polymer block (A) / polymer block (B) / polymer block (A).
[0063] As shown in FIG. 2(C), in the virus inactivation structure according to the second embodiment, at least some of the block copolymer chains 40 are present in a state in which the polymer block (A) is in the base polymer 30 and the polymer block (B) is exposed from the base polymer 30. That is, the virus inactivation structure according to the second embodiment has a structure in which a plurality of loop structures formed in the polymer chain based on the block copolymer chain 40 are exposed on the surface. Specifically, the polymer block (A) is present in the base polymer 30 and a polymer brush structure is formed in which a plurality of polymer chains of the loop structure formed by the polymer block (B) are exposed. In the second embodiment, the polymer block (B) has a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron-donating group. As a result, the virus inactivation structure according to the second embodiment has a high virus inactivation function similar to the polymer brush layer 20 in the first embodiment described above, and further, the high virus inactivation function can be sustained for a long period of time.
[0064] In the virus inactivation structure according to the second embodiment, a block copolymer chain 40 having a structure of polymer block (A) / polymer block (B) / polymer block (A) is used, in which polymer block (A) has a relatively high affinity for base polymer 30, while polymer block (B) has a relatively low affinity for base polymer 30. Therefore, while polymer blocks (A) located on both sides of polymer block (B) remain in base polymer 30, polymer block (B) is exposed from base polymer 30, forming a loop structure of polymer block (B) as shown in Fig. 2(C).
[0065] In addition, in the virus inactivation structure according to the second embodiment, a plurality of block copolymer chains 40 that are not involved in the loop structure shown in FIG. 2(C) are dispersed in the base polymer 30 (see, for example, FIG. 2(B)). Therefore, for example, when a defect occurs in a part of the block copolymer chains 40 that are involved in the loop structure shown in FIG. 2(C), the block copolymer chains 40 located near the defective site among the block copolymer chains 40 dispersed in the base polymer 30 change to one having the loop structure shown in FIG. 2(C), thereby having a self-repairing effect that can compensate for such a defect. Note that, for example, when a configuration is adopted in which a plurality of block copolymer chains 40 are brought into contact with the surface of the base polymer 30 to form a loop structure instead of the method of dispersing a plurality of block copolymer chains 40 in the base polymer 30, when such a defect occurs in the loop structure, a self-repairing effect that compensates for the defect cannot be expected.
[0066] There is no particular limitation on the base polymer 30, and various resins and rubbers can be used without limitation. The resin may be either a thermosetting resin or a thermoplastic resin, and examples of the thermosetting resin include epoxy resin, phenol resin, amino resin, unsaturated polyester resin, polyurethane resin, urea resin, melamine resin, thermosetting polyimide resin, and diallyl phthalate resin.
[0067] Examples of thermoplastic resins include polyolefin-based resins such as polyethylene, polypropylene, polystyrene, and polycycloolefin; vinyl-based resins such as polystyrene, acrylic resin, polyvinyl chloride resin, and polyvinyl alcohol; fluorine-based resins such as polytetrafluoroethylene; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polyethylene naphthalate; and silicone resins such as polydimethylsiloxane.
[0068] Examples of rubber include diene-based rubbers such as butadiene rubber, styrene butadiene rubber, chloroprene rubber, isoprene rubber, natural rubber, nitrile rubber, and butyl rubber; and rubbers other than diene-based rubbers such as ethylene propylene rubber, acrylic rubber, polyether rubber, polyurethane rubber, fluororubber, and silicone rubber.
[0069] Of these resins or rubbers, polystyrene, acrylic resins, silicone resins, and styrene-butadiene rubber are preferred, acrylic resins are preferred, and of the acrylic resins, polybutyl methacrylate is particularly preferred.
[0070] The base polymer 30 preferably has a glass transition temperature (Tg) lower than the use temperature of the composite 10, and specifically, the Tg is preferably 50°C or lower, and more preferably 20°C or lower.
[0071] The block copolymer chain 40 is not particularly limited as long as it comprises a polymer block (A) and a polymer block (B) having a lower affinity for the base polymer 30 than the polymer block (A), and has the polymer block (A) at at least two locations in the block copolymer chain. From the viewpoint of being able to form the loop structure shown in FIG. 2(C) in a process, it is preferable to use a polymer block (B) that is incompatible with the base polymer 30, and it is particularly preferable to use a polymer block (B) that is incompatible with the base polymer 30 and a polymer block (A) that is compatible with the base polymer 30.
[0072] Here, the fact that the polymer block (A) is compatible with the base polymer 30 refers to the following state: That is, when a polymer consisting only of the polymer block (A) is mixed with the base polymer 30 by hot melt mixing, co-solution mixing, or the like, and the resulting mixture is then solidified by cooling or evaporating and removing the solvent, or the like, and the glass transition temperature (Tg) of the obtained sample is measured. If a Tg different from the Tg of the polymer consisting only of the polymer block (A) and the Tg of the base polymer 30 is observed in a temperature range between these, it can be determined that the two are compatible.
[0073] Alternatively, the polymer block (B) being incompatible with the base polymer 30 refers to the following state: That is, when a polymer consisting only of the polymer block (B) is mixed with the base polymer 30 by hot melt mixing, co-solution mixing, or the like, and the resulting mixture is solidified by cooling or evaporating and removing the solvent, or the like, and the glass transition temperature (Tg) of the obtained sample is measured. When no Tg other than the Tg of the polymer consisting only of the polymer block (B) and the Tg of the base polymer 30 is observed, it can be determined that the two are incompatible.
[0074] As the polymer block (A) and the polymer block (B), those having the above-mentioned compatibility with the base polymer 30 may be used. From the viewpoint of being able to form the loop structure shown in FIG. 2(C) in the process, however, regarding the SP values (solubility parameters), the difference between the SP value of the polymer block (A) and the SP value of the polymer block (B) is set to 1.5 (MPa). 1 / 2 It is preferable that the temperature is 3 (MPa) or more. 1 / 2 More preferably, it is 5 (MPa) or more. 1 / 2 It is more preferable that the difference between the SP value of the polymer block (A) and the SP value of the base polymer is 0.5 (MPa) or more. 1 / 2 It is preferable that the temperature is 0.3 (MPa) or less. 1 / 2 More preferably, it is 0.2 (MPa) or less. 1 / 2It is more preferable that the SP value of the polymer block (B) is less than or equal to 1.5 (MPa). 1 / 2 It is preferable that the temperature is 3 (MPa) or more. 1 / 2 More preferably, it is 5 (MPa) or more. 1 / 2 More preferably, it is equal to or greater than this.
[0075] The polymer block (A) is not particularly limited as long as it satisfies the above-mentioned characteristics, and may be selected in relation to the base polymer 30 to be used. Specific examples include those composed of polymer segments that constitute the resins or rubbers exemplified as the resins or rubbers that constitute the base polymer 30 described above.
[0076] The molecular weight (weight average molecular weight (Mw)) of the polymer block (A) portion of the block copolymer chain 40 is not particularly limited, but from the viewpoint of exhibiting sufficient interaction with the base polymer 30 and thereby more appropriately supporting the loop structure formed by the polymer block (B) and thereby further enhancing durability, it is preferably 1,000 to 100,000, more preferably 1,000 to 50,000, and even more preferably 1,000 to 20,000. The most preferred is 2,000 to 20,000.
[0077] The polymer block (B) is not particularly limited as long as it has a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron donating group and satisfies the above-mentioned characteristics, and may be selected in relation to the base polymer 30 used. However, it is preferable that the polymer block is formed by polymerizing a monomer mixture containing a monomer having a specific functional group. As in the first embodiment described above, it is more preferable that the polymer block is formed by polymerizing a monomer mixture containing a monomer having an ammonium group as the specific functional group (more preferably, a monomer capable of introducing an ammonium group into the side chain of the polymer chain, particularly preferably a compound represented by the above general formula (1)). As the monomer having the specific functional group, one type may be used alone, or two or more types may be used in combination. In addition, as a monomer for forming a polymer chain, a monomer copolymerizable with the monomer having the specific functional group (monomer not having the specific functional group) may be used.
[0078] Furthermore, similarly to the above-described first embodiment, instead of the compound represented by the above general formula (1), or together with the compound represented by the above general formula (1), for example, a (meth)acrylic acid-based monomer, a styrene-based monomer, a monofunctional monomer having one addition-polymerizable double bond, a hydrophobic monomer, a hydrophilic monomer, a monomer having a carboxyl group or a group that can be easily converted to a carboxyl group in a side chain, or the like may be used.
[0079] The molecular weight (weight average molecular weight (Mw)) of the polymer block (B) portion of the block copolymer chain 40 is not particularly limited, but the molecular weight of the polymer block (B) portion is closely related to the loop length (the length of the loop constituting the loop structure) formed. If the molecular weight of the polymer block (B) portion is large, the loop length formed on the surface of the composite 10 is also large. That is, the polymer loop layer (the layer consisting of the loop structure formed by the polymer block (B) portion) is made thicker. On the other hand, if the molecular weight of the polymer block (B) portion is small, the polymer loop layer is thin. Considering the phenomenon of destruction of the loop brush due to the unevenness of the sliding surface facing the loop brush layer, the molecular weight (weight average molecular weight (Mw)) of the polymer block (B) portion is preferably 1,000 to 200,000, more preferably 2,000 to 100,000, even more preferably 3,000 to 50,000, and particularly preferably 3,000 to 20,000.
[0080] The synthesis method of the block copolymer chain 40 is not particularly limited, but when the block copolymer chain 40 is an ABA type block copolymer chain consisting of polymer block (A) / polymer block (B) / polymer block (A), it can be synthesized by the following method. That is, a method of forming polymer block (A) on both sides of polymer block (B) by polymerizing a monomer that forms polymer block (A) in the presence of polymer block (B), a method of polymerizing a monomer that forms polymer block (B) in the presence of polymer block (A) and then further polymerizing a monomer that forms polymer block (A), etc. can be mentioned. As a method that allows control of the molecular weight of each block and obtains a block copolymer with a narrow molecular weight distribution, the living radical polymerization method can be used extremely preferably. Among them, the atom transfer radical polymerization method can be used particularly preferably.
[0081] The polymer block (A) and the polymer block (B) may be directly bonded to each other, or may be bonded to each other via a monomer other than the monomer forming the polymer block (A) and the monomer forming the polymer block (B) or an oligomer block composed of such a monomer. The multiple polymer blocks (A) contained in the block copolymer chain 40 may be substantially the same polymer block (i.e., a block composed of substantially the same monomer units) or may be different polymer blocks. Furthermore, even when the block copolymer chain 40 contains multiple polymer blocks (B), the multiple polymer blocks (B) may be substantially the same polymer block (i.e., a block composed of substantially the same monomer units) or may be different polymer blocks.
[0082] In the second embodiment, the ionic conductivity of the polymer brush layer formed by the plurality of block copolymer chains 40 is preferably 5.0×10 -1 S / m or less, and more preferably 1.0×10 -1 S / m or less, more preferably 5.0×10 -2 S / m or less, and although there is no particular lower limit, it is preferably 1.0×10 -4 The ionic conductivity of the polymer brush layer can be measured by the same method as in the first embodiment described above.
[0083] According to the second embodiment, the polymer brush structure is provided with a plurality of exposed polymer chains of a loop structure formed by the polymer block (B), and the polymer block (B) has a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron donating group. Therefore, as in the above-mentioned first embodiment, the polymer brush structure made of the polymer block (B) exposed in a loop shape has a specific functional group, which makes it easy to fuse with the envelope constituting the virus, and furthermore, since it is composed of a plurality of polymer chains, it exhibits a high osmotic pressure, and thus it can be said that it exhibits a high virus inactivation function. In addition, since the polymer brush structure made of the polymer block (B) is composed of a polymer brush structure made of a plurality of polymer blocks (B), it can stably exhibit such a high virus inactivation function without accompanying structural changes, and therefore it can be said that the high virus inactivation function can be sustained for a long period of time.
[0084] In the second embodiment, an ABA type block copolymer chain consisting of polymer block (A) / polymer block (B) / polymer block (A) is used as the block copolymer chain 40, thereby exposing a plurality of polymer chains having a loop structure formed by the polymer block (B), and a structure having a polymer brush structure is exemplified. However, an AB block copolymer chain consisting of polymer block (A) / polymer block (B) may be used, and thereby the polymer block (B) may be exposed without forming a loop structure.
[0085] <Third embodiment> Next, a third embodiment of the present invention will be described. Fig. 3 is a diagram showing a virus inactivating structure according to a third embodiment of the present invention. As shown in Fig. 3, the virus inactivating structure according to the third embodiment is a branched polymer 50. As shown in Fig. 3, the branched polymer 50 has a structure in which a plurality of polymer graft chains (side chains) 52 branch off from a linear main chain (a linear polymer chain that serves as the main chain) 51 as a substrate. The branched polymer 50 has a shape like a bottle brush (a cleaning brush for cleaning containers having a bottle structure).
[0086] As described above, the branched polymer 50 has a branched polymer structure in which a plurality of side chains 52 branch off from a linear main chain 51, and the main chain 51 and the side chain 52 are each formed by linking a plurality of repeating units each including at least a carbon atom and a hydrogen atom. In the branched polymer 50, the side chain 52 has a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron-donating group, and the branched polymer 50 has such a side chain 52 and thus has a virus inactivation function.
[0087] The number average degree of polymerization of the main chain 51 is preferably 10 to 10,000, more preferably 10 to 1,000, and further preferably 10 to 100. The number average degree of polymerization of the main chain 51 is not particularly limited, but can be determined by measuring the number average molecular weight of the main chain precursor before the introduction of the side chain 52, and dividing the measured number average molecular weight by the monomer unit molecular weight.
[0088] The side chain 52 may be linear or may have a branched or crosslinked structure. The number average degree of polymerization of the side chain 52 is preferably 1 to 1.00, more preferably 1 to 50, and even more preferably 5 to 20. The method for measuring the number average degree of polymerization of the side chain is not particularly limited. For example, in the step of synthesizing the branched polymer 50, when a reaction is carried out to extend the side chain 52 from the main chain 51, a small amount of a low molecular weight initiator (e.g., an organic compound having a halogen-substituted carbon group) is added to the reaction system so that a free polymer having a repeating structure common to the polymer chain of the side chain 52 is simultaneously synthesized, and the number average degree of polymerization measured for the free polymer can be taken as the number average degree of polymerization of the side chain 52.
[0089] The number average molecular weight (Mn) of the entire branched polymer 50 including the main chain 51 and the side chains 52 is preferably 1,000 to 10,000,000, more preferably 1,000 to 1,000,000, and further preferably 5,000 to 500,000. The number average molecular weight of the entire branched polymer 50 can be measured by gel permeation chromatography in terms of polystyrene.
[0090] The density of side chains branching from the main chain is, in terms of the number per 1 nm of main chain path length (chains / nm), preferably 1 chain / nm or more, more preferably 2 chains / nm or more, and even more preferably 3 chains / nm or more. Here, the density of the side chains can be determined from the grafting efficiency.
[0091] The branched polymer 50 used in the third embodiment is not particularly limited as long as it has a structure in which a plurality of side chains 52 are branched from a linear main chain 51 as a base, as shown in FIG. 3, and the plurality of side chains 52 have a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron donating group. The branched polymer 50 can be produced, for example, by graft polymerizing a monomer mixture containing a monomer having a specific functional group to a polymer for forming the main chain 51 by a known graft polymerization method. In addition, the branched polymer 50 is preferably produced by graft polymerizing a monomer mixture containing a monomer having an ammonium group as the specific functional group (more preferably, a monomer capable of introducing an ammonium group into the side chain of the polymer chain, particularly preferably a compound represented by the above general formula (1)) as the specific functional group, as in the above first embodiment. The monomer having the specific functional group may be used alone, or two or more types may be used in combination. In addition, a monomer copolymerizable with the monomer having the specific functional group (monomer not having the specific functional group) may be used as the monomer for forming the polymer chain.
[0092] Furthermore, similarly to the above-described first embodiment, instead of the compound represented by the above general formula (1), or together with the compound represented by the above general formula (1), for example, a (meth)acrylic acid-based monomer, a styrene-based monomer, a monofunctional monomer having one addition-polymerizable double bond, a hydrophobic monomer, a hydrophilic monomer, a monomer having a carboxyl group or a group that can be easily converted to a carboxyl group in a side chain, or the like may be used.
[0093] In the third embodiment, the branched polymer 50 may be one in which a plurality of branched polymers 50 form a crosslinked structure, or one in which a plurality of branched polymers 50 are bonded to each other by ionic bonds, hydrogen bonds, hydrophobic interactions, or the like. Alternatively, a substrate or a filler may be used, and a polymerization initiator group may be introduced to the surface of the substrate or filler, and a polymerization reaction may be carried out on the substrate or in a state containing the filler, thereby forming a composite of the branched polymer 50 on the substrate or with the filler. When a plurality of branched polymers 50 are composited on the substrate, a polymer brush layer made of a plurality of branched polymers 50 can be formed on the substrate. In this case, the ionic conductivity of the polymer brush layer made of a plurality of branched polymers 50 is preferably 5.0×10 -1 S / m or less, and more preferably 1.0×10 -1 S / m or less, more preferably 5.0×10 -2 S / m or less, and although there is no particular lower limit, it is preferably 1.0×10 -4 The ionic conductivity of the polymer brush layer can be measured by the same method as in the first embodiment described above.
[0094] The branched polymer 50, which is a virus inactivation structure according to the third embodiment, has a structure in which a plurality of polymer graft chains (side chains) 52 are branched from a main chain 51, and the side chains 52 have a specific functional group selected from an ionic group, a nonionic hydrophilic group, and an electron donating group. Therefore, as in the above-mentioned first embodiment, the branched polymer 50 is easily fused with the envelope constituting the virus due to the action of the specific functional group contained in the side chains 52, and furthermore, since it is composed of a plurality of polymer chains, it exhibits a high osmotic pressure, and thus exhibits a high virus inactivation function. In addition, since the branched polymer 50 has a bottle brush-like structure with a plurality of side chains 52, it can stably exhibit such a high virus inactivation function without accompanying structural changes, and therefore it can be said that the high virus inactivation function can be sustained for a long period of time. EXAMPLES
[0095] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0096] <Example 1> (Formation of polymer brush layer) Surface-initiated atom transfer radical polymerization (ATRP) of N,N-diethyl-N-(2-methacryloylethyl)-N-methylammonium bis(trifluoromethylsulfonyl)imide (DEMM-TFSI) was carried out as follows. That is, first, 26.0 mg (0.13 mmol) of 2,2'-bipyridine (Bipy), 1.96 g of N,N-diethyl-N-(2-methacryloylethyl)-N-methylammonium bis(trifluoromethylsulfonyl)imide (DEMM-TFSI), and 8.0 g of acetonitrile were placed in a flask, and the solution was degassed by bubbling with argon for 10 minutes. The flask was then transferred to a glove box purged with argon, and 5.2 mg (0.052 mmol) of Cu(I)Cl and 0.78 mg (0.0058 mmol) of Cu(II)Cl2 were added, and a three-way stopcock was attached to the flask. Then, while keeping the stopper closed and sealed, the flask was removed from the glove box and stirred in an oil bath at 60 °C to completely dissolve copper and Bipy. The flask was then transferred to a glove box, and the solution was filtered with a membrane filter (pore size: 0.2 μm). A vacuum pump was then used to volatilize and remove the acetonitrile. The reason for adding acetonitrile in the above procedure is to reduce the viscosity of the solution and promote the dissolution of copper and Bipy as a ligand. In addition, in order to suppress the precipitation of copper chloride during the polymerization process, the reaction was carried out using a 10% excess amount of ligand (Bipy) relative to the required molar amount in terms of the molar amount relative to copper. Next, 8.0 g (16.6 mmol) of DEMM-TFSI and 0.65 mg (0.0033 mmol) of ethyl 2-bromoisobutyrate (2-(EiB)Br) were placed in another Schlenk tube, and the mixture was degassed by bubbling with argon for 20 minutes. The resulting solution was placed in the Schlenk tube and the flask and mixed to prepare a non-volatile ATRP polymerization solution. The molar composition ratio of the resulting ATRP polymerization solution was [DEMM-TFSI]0 / [2-(EiB)Br]0 / [Cu(I)Cl]0 / [Cu(II)Cl2]0 / [Bipy]0=5000 / 1 / 20 / 5 / 50.
[0097] Next, the ATRP polymerization solution thus obtained was filtered, and the filtered ATRP polymerization solution was centrifuged at 500×g for 10 minutes using a centrifuge installed in a glove box to perform a degassing operation. The filtration and degassing operations are performed to prevent undissolved solid components of copper chloride or air bubbles mixed in during the preparation of the solution from adhering to a substrate such as a silicon wafer or glass, which would prevent the formation of a polymer brush on that portion.
[0098] Next, in a glove box, the ATRP polymerization solution, which had been filtered and degassed, was applied onto a silicon wafer on which an ATRP initiator group had been immobilized using (2-bromo-2-methyl)propionyloxypropyltriethoxysilane (BPE) as an immobilization initiator. Then, an ATRP polymerization reaction was carried out in an incubator (installed in a glove box) set at a temperature of 70°C. The ATRP polymerization solution prepared above was prepared only with non-volatile components and had a relatively high viscosity, so it was maintained as a liquid layer with a thin liquid film on the silicon wafer until the polymerization was completed. In this ATRP polymerization reaction system, the polymerization conversion rate of the monomer reached 99% after 70 hours, and a polymer brush layer having multiple polymer chains with a number average molecular weight of 1,826,000 and a molecular weight distribution (Mw / Mn) of 1.20 was formed on the silicon wafer. The obtained polymer brush layer had a dry film thickness T measured by spectroscopic ellipsometry. b The thickness of the film (after drying in a vacuum at 25°C for 1 hour) was 515 nm, and the graft density was 0.15 chains / nm, as measured by the method described above. 2 The surface occupancy rate was calculated to be 35%. The average molecular chain length L of the polymer chains constituting the polymer brush layer, calculated by the above method, was p for the thickness of the polymer brush layer T b Ratio of (T b / L p ) was 0.41, and the ionic conductivity of the polymer brush layer measured by the four-terminal method (using a resistivity meter (Loresta, manufactured by Nitto Seiko Analytech Co., Ltd.)) was 1.60 × 10 -2Separately, a polymer of DEMM-TFSI was prepared and dispersed in water at pH=7 at 1% by weight, and the absorbance was measured, resulting in an absorbance of 0.3 or less, indicating water solubility.
[0099] (Evaluation of viral inactivation) After the above-obtained silicon wafer (1 cm x 1 cm) on which the polymer brush layer was formed was sterilized, 3 μL of virus liquid (bovine herpes virus liquid) was dropped onto the surface on which the polymer brush layer was formed, and the virus liquid was spread over the surface on which the polymer brush layer was formed, covered with a cover glass, and left to stand at room temperature for 5 minutes. After 5 minutes had elapsed, the silicon wafer on which the polymer brush layer was formed was placed in a test tube together with 500 μL of culture liquid (MEM), and stirred for 10 seconds with a vortex mixer to liberate the virus adhering to the surface of the polymer brush layer into the culture liquid. Next, a portion of the culture liquid was extracted, and the extracted culture liquid was inoculated into cells, and the number of plaques detected was counted to evaluate the virus inactivation effect. In addition, to evaluate the virus inactivation effect, the same measurement as above was performed on a glass plate without a polymer brush layer, and the number of plaques counted was compared. As a result, the number of plaques detected on the silicon wafer with the polymer brush layer (average: 11) was 7% of the number of plaques detected on the glass plate without the polymer brush layer (average: 157). In other words, the number of viruses was reduced by 93%.
[0100] In addition, the same measurement as above was performed, but the standing time was changed from 5 minutes to 30 minutes. As a result, the number of plaques detected on the silicon wafer with the polymer brush layer (average: 1.3) was 1.2% of the number of plaques detected on the glass plate without the polymer brush layer (average: 104.3). In other words, the number of viruses was reduced by 98.8%.
[0101] Furthermore, when the silicon wafer with the polymer brush layer formed thereon that had been subjected to the above-mentioned evaluation of virus inactivation (left to stand for 30 minutes) was washed with distilled water and the above-mentioned evaluation of virus inactivation was performed again (left to stand for 30 minutes) (i.e., evaluation by reuse was performed), the number of plaques detected on the silicon wafer with the polymer brush layer formed thereon was less than 10% of the number of plaques detected on the glass plate without the polymer brush layer formed thereon, resulting in a reduction in the number of viruses by 90% or more. When washing with a 70% ethanol aqueous solution instead of distilled water was performed and the evaluation was carried out in the same manner as above, the number of plaques detected on the silicon wafer with the polymer brush layer was less than 10% of the number of plaques detected on the glass plate without the polymer brush layer, which means that the number of viruses was reduced by 90% or more.
[0102] From the above, it can be confirmed that a polymer brush containing multiple polymer chains having specific functional groups selected from ionic groups, nonionic hydrophilic groups, and electron-donating groups can achieve high virus inactivation function and, further, that such high virus inactivation function can be sustained over the long term.
[0103] <Example 2> (Formation of polymer brush layer) A polymer brush layer was formed on silica particles in the same manner as in Example 1, except that (2-bromo-2-methyl)propionyloxyhexyltriethoxysilane (BHE) was used as the immobilization initiator instead of (2-bromo-2-methyl)propionyloxypropyltriethoxysilane (BPE), and silica particles were used instead of silicon wafers. The polymer brush layer obtained was quantified by thermogravimetric analysis, and the weight fraction of the polymer content was 8.9%. The graft density measured by the above-mentioned method was 0.15 chains / nm. 2In Example 2, taking into consideration the manufacturing conditions and the like, the number average molecular weight and molecular weight distribution (Mw / Mn) of the polymer chains constituting the polymer brush layer, the dry film thickness T b , the thickness of the polymer brush layer T b Ratio of (T b / L p ) and the ionic conductivity of the polymer brush layer are almost the same as those in Example 1.
[0104] (Evaluation of viral inactivation) 1.0 g of the silica particles with the polymer brush layer formed was dispersed in 200 mL of a solvent consisting of an equal volume mixture of 0.5 M acetonitrile acetate and water to obtain an acetic acid dispersion of the silica particles with the polymer brush layer formed. Then, 0.925 mL of the acetic acid dispersion of the silica particles with the polymer brush layer formed, 100 μL of a virus solution (bovine herpes virus solution), and 1.475 mL of phosphate buffered saline (PBS) were placed in a test tube to prepare a test solution. Then, 25 μL of the obtained test solution (prepared sample) was collected, and the sample was shaken for 1 hour, and 25 μL of the test solution after shaking for 1 hour (1-hour shaken sample) was collected, and the sample was shaken for 1 hour, and 25 μL of the test solution after shaking for 1 hour (2-hour shaken sample) was collected. The collected post-preparation sample, 1-hour shake sample, and 2-hour shake sample were then diluted 10,000-fold with culture medium (MEM) and inoculated onto cells. After standing for 1 hour, the cells were overlaid with methylcellulose medium and cultured for 2 days, after which the virus inactivation effect was evaluated in the same manner as in Example 1. In Example 2, a sample using silica particles without a polymer brush layer was also prepared under the same conditions and used as a comparison subject. As a result, the same virus inactivation function as in Example 1 was confirmed in Example 2.
Claims
1. A virus inactivation material having a virus inactivation function, comprising a polymer brush layer on a substrate, the polymer brush layer including a plurality of polymer chains each having a functional group selected from an ionic group, a nonionic hydrophilic group, and an electron-donating group, A virus inactivation material having a virus inactivation function, wherein the polymer chain is introduced onto a substrate by a surface-initiated living radical polymerization method using a monomer containing at least a compound represented by the following general formula (1): 【Chemistry 3】 [In the above general formula (1), m represents an integer of 1 or more and 10 or less. n represents an integer of 1 or more and 5 or less. R 1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. R 2 , R 3 , and R 4 represent alkyl groups having 1 to 5 carbon atoms. R 2 , R 3 , and R 4 may contain one or more heteroatoms selected from an oxygen atom, a sulfur atom, and a fluorine atom, and two or more of R 2 , R 3 , and R 4 may be linked to form a cyclic structure. In addition, Z - represents a monovalent anion.]
2. The virus inactivating material according to claim 1 , wherein the plurality of polymer chains are water-soluble.
3. 3. The virus inactivating material according to claim 1, wherein a plurality of the polymer chains are fixed onto the substrate by covalent bonds to form a polymer brush layer.
4. The average molecular chain length L of the polymer chains constituting the polymer brush layer p The thickness T of the polymer brush layer b The ratio (T b / L p 4. The virus inactivating material according to claim 1, wherein the ratio of the concentration of the inactivating agent to the concentration of the virus is 0.001 to 0.
6.
5. 5. The virus inactivating material according to claim 1, wherein the substrate is a fiber, a single fiber, a twisted yarn, a woven fabric, a nonwoven fabric, a cut fiber, a hollow fiber, glass, a metal, or a processed product thereof.
6. The graft density per unit area of the polymer chain is 0.12 to 0.25 chains / nm 2 and an occupied area ratio to the surface area of the substrate is 20 to 40% in terms of an occupation rate per cross-sectional area of the polymer.
7. The ionic conductivity of the polymer brush layer is 5.0×10 -1 The virus inactivating material according to any one of claims 1 to 6, having a viscosity of 0.5 S / m or less.
8. The virus inactivating material according to any one of claims 1 to 7, wherein the polymer chains fuse with an envelope constituting a virus, causing the envelope to be cleaved, and thereby RNA inside the virus is expelled to the outside by the osmotic pressure of the polymer chains, thereby inactivating the virus.
9. 9. The virus inactivating material according to any one of claims 1 to 8, wherein the number average molecular weight (Mn) of the polymer chain is from 100,000 to 10,000,000 and the molecular weight distribution (Mw / Mn) is 1.25 or less.
10. 10. Use of the virus inactivation material according to any one of claims 1 to 9 for inactivating viruses.
Citation Information
Patent Citations
Dot printer
JP1983092570A
Antiviral pharmaceutical compositions
JP2007513959A
Antiviral method
JP2009526060A
Novel anti-adhesion technology using RAFT polymerization
JP2019521209A
Antiviral or virus-inactivating agent
JP2020128342A